REGULATORY AND INSTITUTIONAL FOUNDATIONS OF SOCIAL SECURITY REGULATION AND PROVISION IN UKRAINE - VARVUS, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article analyzes the importance of social security in Ukraine in the context of regulatory compliance and alignment with international standards. It has been determined that social security is foundational to the decent life of citizens and holds significance for the international image of the country. The ways in which constitutional norms facilitate the protection of citizens' rights and freedoms are disclosed, highlighting the role of the state in supporting democratic development and social justice. A comprehensive approach to the development of regulatory foundations for social security has been proposed, incorporating innovative strategies for responding to social risks. It has been established that effective regulation not only fosters social stability but also higher living standards. The impact of national security strategies and economic reforms on social stability has been analyzed, illuminating the need for a balance between economic stability and social security. Critical issues in managing social security in Ukraine have been identified, including inadequate leadership responsibility and a lack of clear definition of social security in the current National Security Strategy. Recommendations for improving legislative and regulatory foundations, enhancing coordination among authorities, and strengthening institutional support for state management of social security have been made. It has been established that social security impacts the level of life and health of citizens, highlighting the necessity of its provision as a state policy priority. New approaches to policy development and implementation have been proposed that strengthen social protection and public health development amidst managerial modernization. The effectiveness of tools that enhance cultural, educational, and economic standards has been developed and assessed, facilitating the integration of international practices into the national strategy for social security. It has been proven that investigating the understanding of social security as a key element of national security and state responsibility is important before its citizens, especially in the challenges facing modern Ukraine.
Keywords: security; social security; regulation; legislative foundation; institutional development